INTERVENTION OF “HEALTHY MENSTRUATION” PACKET TO DYSMENORHEA INTENSITY IN PATRA MANDIRI 1 HIGH SCHOOL PALEMBANG - Dina Anggreni; Jum Natosba; Trilia Trilia (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Dysmenorhea is pain that feel during fi rst or second day in menstruation cycles. The purpose of this study was to identify the infl uence of healthy menstruation packet to dysmenorhea that feel by adolescent in Patra Mandiri 1High School Palembang. Method. This study used experiment study with pre-post test with control group design. Total samples were acquired by non probability sampling with simple sampling. Total samples of this study were 34 respondents with 17 respondents in intervention group and 17 respondents in control group. Instrument of this study used questionnaires and observation. Result. This study showed that there was difference of dysmenorhea before and after did healthy menstruation packet in intervention group (p value=0,000). Discussion. For school can increase knowledge about reproduction healthy in women especially related to handling dysmenorhea and provision health education through the integration with health institute.Keyword: dysmenorhea, healthy menstruation packet, reproduction